Two New Species of Pandanus Subg. Rykia Sect. Rykia (Pandanaceae)from Sarawak, Borneo - Haziah, Musa; Akmal, Raffi; Zinnirah, Shabdin; Meekiong, Kalu; Nur Safinas, Jelani (Universiti Putra Malaysia Press, 2026)
Two new Pandanus species are herein described: Pandanus mansio Haziah, Raffi, Shabdin & Meekiong and P. sakek Haziah, Raffi, Shabdin & Meekiong. These species were discovered in Sematan, Lundu, Kuching, Sarawak. Pandanus mansio closely resembles Pandanus leuconotus but differs by its taller stature, longer and narrower leaves with an unarmed mid-section of the leaf margin, pinkish-orange to green leaf base and ovoid cephalium with long peduncle. Meanwhile, P. sakek is morphologically similar to P. kamiae but distinguishable by its shorter, narrower and subcoriaceous leaves and smaller cephalium bearing longer styles, including falcate styles at apical drupes. With these additions, Sarawak now harbours five species of Pandanus subg. Rykia sect. Rykia.